The role of neuromarketing in the development of tourism (Journal of Geography and Environmental Management, 2018)
Currently, under the conditions of oversaturation of the market in goods and services, there is a question about the search for new trends in marketing activities, in particular in the field of work with consumers, improve the efficiency of the impact on the consumer and determine the degree of perception of the information. In this regard, the most relevant and innovative direction of marketing today is neuromarketing, which uses human brain research to study the behavior of customers. If classical marketing is built on the evaluation of subjective data, neuromarketing relies on an analysis of those human reactions that manifest themselves spontaneously and uncontrollably. With the help of neuromarketing, you can identify what stimulates the consumer to purchase a particular product or service. The use of methods of neuromarketing in the field of tourism is also relevant. The article examines the theoretical foundations of neuromarketing, presents various points of view of Russian and foreign scientists on the concept of “neuromarketing”, analyzes the existing terminology. At the same time, the neuromarketing and tourism nexus, the distinctions between the concepts of “marketing” and “neuromarketing” are revealed, data on international neuromarketing research and its results are given. SWOT analysis of the use of neuromarketing tools in tourism has been compiled.